The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.omtm.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Anti-high Mobility Group Box 1 Antibody Ameliorates Albuminuria in MRL/lpr Lupus-Prone Mice

Abstract: We evaluated the efficacy of a neutralizing anti-high mobility group box 1 (HMGB1) monoclonal antibody in MRL/lpr lupus-prone mice. The anti-HMGB1 monoclonal antibody (5 mg/kg weight) or class-matched control immunoglobulin G2a (IgG2a) was administered intravenously twice a week for 4–15 weeks. Urine albumin was monitored, and histological evaluation of the kidneys was conducted at 16 weeks. Lymphadenopathies were evaluated by 1-(2′-deoxy-2′-[18F]fluoro-β-D-arabinofuranosyl)cytosine ([18F]FAC) positron emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Abbreviations ADM: Adriamycin; aGVHD: Acute GVHD; ALCLs: Anaplastic large-cell lymphomas; allo-HSCT: Allogeneic HSCT; AML: Acute myeloid leukemia; Ara-C: Cytosine arabinoside; ATO: Arsenic trioxide; ATRA: All-trans-retinoic acid; AP1: Activator protein 1; APL: Acute promyelocytic leukemia; ATL: Adult T cell In vitro Inhibits HMGB1-induced autophagy and increases the sensitivity of leukemia cells to chemotherapy [175] mAb (2G7) In vivo Improves arthritis, LN and drug-induced liver injury [176][177][178] s-RAGE In vivo Blocks the HMGB1-RAGE signaling pathway [179] HMGB1 A-box In vitro Inhibits the proinflammatory actions of the B-box [5] TAT-HMGB1A In vitro Reduces secretion of endogenous HMGB1 protein [180] GL Decreases serum HMGB1 levels and improves SIRS in hematological malignancies; improves DIC in AML; inhibits HMGB1 protein secretion and inhibits I-κB phosphorylation [190][191][192]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abbreviations ADM: Adriamycin; aGVHD: Acute GVHD; ALCLs: Anaplastic large-cell lymphomas; allo-HSCT: Allogeneic HSCT; AML: Acute myeloid leukemia; Ara-C: Cytosine arabinoside; ATO: Arsenic trioxide; ATRA: All-trans-retinoic acid; AP1: Activator protein 1; APL: Acute promyelocytic leukemia; ATL: Adult T cell In vitro Inhibits HMGB1-induced autophagy and increases the sensitivity of leukemia cells to chemotherapy [175] mAb (2G7) In vivo Improves arthritis, LN and drug-induced liver injury [176][177][178] s-RAGE In vivo Blocks the HMGB1-RAGE signaling pathway [179] HMGB1 A-box In vitro Inhibits the proinflammatory actions of the B-box [5] TAT-HMGB1A In vitro Reduces secretion of endogenous HMGB1 protein [180] GL Decreases serum HMGB1 levels and improves SIRS in hematological malignancies; improves DIC in AML; inhibits HMGB1 protein secretion and inhibits I-κB phosphorylation [190][191][192]…”
Section: Discussionmentioning
confidence: 99%
“…Several anti-HMGB1 monoclonal antibodies have been developed for clinical applications. The monoclonal antibody 2G7 binds to the HMGB1 epitope containing aa 53-63 and has shown beneficial therapeutic effects in experimental models of arthritis, lupus nephritis (LN) and drug-induced liver injury [176][177][178].…”
Section: Anti-hmgb1 Antibodiesmentioning
confidence: 99%
“…TLR2 and TLR4 are expressed not only in parenchymal cells but also in infiltrating neutrophils and mononuclear phagocytes, including macrophages and dendritic cells [137]. The HMGB1 (high mobility group box 1) protein, which binds DNA and the lupus autoantigen released under inflammation, can induce the activation of NF-κB in a TLR2-dependent and TLR4-RAGE-dependent manner in mononuclear phagocytes and neutrophils [138][139][140][141][142][143] as well as in mesangial cells [144]. Mesangial cells and podocytes in humans are characterized by the expression of TLR4 [145].…”
Section: Lupus Nephritismentioning
confidence: 99%
“…It is also important to mention that the key findings related to NETs and their role in autoimmune diseases, for example, systemic lupus erythematosus (SLE) have been made in a rodent model [113][114][115]. Furthermore, it has also been shown that treatment with HMGB1 antibody inhibited the infiltration of neutrophils and, subsequently, NET formation without altering the antibody production in lupus-prone mice [116]. The antibody treatment additionally suppressed the NET manifestation in the glomerulus [116].…”
Section: Murinaementioning
confidence: 99%
“…Furthermore, it has also been shown that treatment with HMGB1 antibody inhibited the infiltration of neutrophils and, subsequently, NET formation without altering the antibody production in lupus-prone mice [116]. The antibody treatment additionally suppressed the NET manifestation in the glomerulus [116]. The detection of NETs in lesions of patients suffering from MPO-antineutrophil cytoplasmic antibody (ANCA) associated vasculitis (MPO AVV) suggested an additional role of NETs in this autoimmune condition [41].…”
Section: Murinaementioning
confidence: 99%